Pendidikan Karakter Dalam Era Milenial: Menjawab Tantangan Global Dan Lokal - Janes Sinaga; Ramlen Woran; Juita Lusiana Sinambela (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2021)
Character education is increasingly relevant in the millennial era, where the younger generation faces complex global and local challenges. This research aims to explore the role and urgency of character education in facing these challenges. In the context of social and technological change, character education is an important basis for forming a strong and competitive generation. This research uses qualitative methods with literature review. The importance of character education in facing the challenges of globalization and the various perspectives of values in society are analyzed. The influence of technology and social media is also a new challenge in building the character of the millennial generation. Strategies to ensure effective character education in dealing with globalization and local currents are also discussed. This research provides in-depth and useful insights for education practitioners, policy makers, and all parties who care about the character building of quality and competitive millennial generations. Through a deep understanding of the importance of character education in the millennial era, it is hoped that the younger generation can grow as individuals with integrity, globally competitive and respect local values that strengthen national identity.